(untitled) (El-Wahat Journal for Research and Studies, 2020)
This Article Deals With The Poetic Evidence In The Book Of The Interpretation Of Sheikh Mohammed Bin Ibrahim Said Kaabache Nafahat Rahman In Riyadh Koran, As It Sheds Light On The Concepts Of Poetry As Well As Explanation To Expose The Differences Between The Evidence And Arguments, Examples And Reasoning, And Finally To Employ Poetic Evidence In The Interpretation Of Sheikh Kaabache It Is A Gain For The Language Lesson Itself, And Contributes To The Translation Of Interpretation Into Scientific Gains Expressed By Language Uses In Deferent Contexts Key Words - Verses ,Quotation, Interpretation Of The Holy Qur’an, Methodology